The Principle Of Commitment To Professional Secrecy In The Algerian Labor Law - Baadj, Amira (Journal of Human Sciences, 2023)
According to the Algerian labor law, the work contract and the good faith that applies to all contracts; confidentiality at work considered one of the most basic obligations of the employee‚ Professional secret considering a grave error this including in article 73 of 90-11 law ‚this means that the worker who doesn't committed to the professional secret may be punished by disciplinary dismissal unless permission is obtained from supreme authority or by law. Disclosure of the professional secret would undermine the trust between the two parties to the work relationship to be stable in the event of disclosure of the secret professional by any means.